Controls on deep-water slope channel complex fill, propagation, stacking, and orientation in the Middle Eocene-Oligocene Kirkgecit Formation, Elazig, eastern Turkey - Celik, Hasan; Cronin, Bryan Thomas (Tubitak Scientific & Technological Research Council Turkey, 2020)
Deep-water channels are well-exposed along the northern margin of the east-west oriented Late Paleocene to Oligocene Elazig Basin of eastern Turkey. The deep-water slope channel complexes are characterised by their association with prominent normal faults, where they seem to have controlled their geometries at the northern margin. The channels were fed by coarse-grained sediment shed by subaqueous gravity flows such as high and low-density turbidity currents, and both cohesive and noncohesive debris flows, from elevated hinterland across narrow shelves and through canyons and gullies into the channels. The faulting and subsequent folding along the northern basin margin created a significantly irregular deep-water slope, and these gravity flows were deflected around, and ponded against this topography. The nature of the impact of seafloor topography, created both before and during channel activity, was examined to create a scheme that documents the range of such effects. Detailed field mapping in this semidesert area shows that these slope channel complexes were strongly controlled by block fault topography generated during early basin evolution in the Late Paleocene, and again during fold development from thrust nappe emplacement during basin filling in the Late Middle Eocene when the Hazar-Maden Basin closed in the south. Four styles of slope channel complex-fold interaction have been recognised: deflection, blocking, diversion, and confinement. In each style of interaction, folding and faulting controlled both channel complex planform geometry and architectural style of the channel fills. In addition to seafloor topography inherited from these earlier phases of compression, subsequent gravitational collapse on the northern basin margin also created normal fault-bound blocks that locally controlled turbidity current pathways and channel complex orientation. It has also been shown that the orientation of the slope channel complexes within mudprone slope sequences has later controlled the orientation of younger fold axis in the Middle Eocene. The study illustrates very well-exposed examples of complex seafloor topography generated by compressional and extensional tectonics, and the impact this has had on slope channel complex evolution.
Keywords: Deep-water slope channel complexes; Eocene turbidites; Elazig Basin; Marik Member; eastern Turkey